Lymphadenitis as a Rare Side Effect of H1N1 Vaccine in a Child - Zuhal Gundogdu; Mualla Seyhogullari (Case Reports in Medicine)
We present a 5-year-old boy who had the complaint of swelling and pain on the right vaccine shot and right axillary areas. The right axillary area was diagnosed as reactive lymphadenitis, which we believe is a rare local side effect of the swine flu vaccine. The key message to take away from this case is that the patient had lymphadenitis as a local side effect of the swine flu vaccine. Lymphadenitis should be reported as a possible local side effect of the swine flu vaccine.